Parallel fast and slow motor inhibition processes in Joint Action coordination - Cardellicchio, Pasquale; Dolfini, Elisa; Fadiga, Luciano; D'Ausilio, Alessandro (Cortex, 2020)
Motor inhibition is essential to adapt to an ever-changing environment and to noise in state prediction. As a consequence, inhibitory motor control must also play a key role during Joint Action (JA) tasks, where the motor system has to further integrate inferences about others' action. Yet, very little research has been carried out on the contribution of motor inhibition in JA tasks. Here, we used an interactive task in which subjects were required to open a bottle with one hand. The bottle was held and stabilized by a co-actor (JA) or by a mechanical holder (vice clamp, no-JA). A first motion capture study characterized the reaching and grasping kinematics of the two conditions. In a second study, by means of Transcranial Magnetic Stimulation (TMS), we measured (i) corticospinal excitability (CSE), (ii) cortical silent period (cSP) and (iii) short-interval intracortical inhibition (sICI), during the reaching phase of the task. These latter two indexes respectively reflect slow corticospinal (GABAb-mediated) and fast intracortical (GABAa-mediated) inhibition. We found no modulation for CSE, while cSP was increased and intracortical inhibition was downregulated during JA. Interestingly, the cSP correlated with partners' predictability as a whole and with partners’ behaviour in the previous trial. These results, beside showing clear dissociation between fast and slow inhibition during JA, also shed new light on the predictive role played by corticospinal inhibitory mechanisms in online mutual behavioural co-adaptation.